Science for Policy: A Case Study of Scientific Polarization, Values, and the Framing of Risk and Uncertainty. Issue 6 (10th December 2018) - Mason‐Renton, Sarah; Vazquez, Marco; Robinson, Connor; Oberg, Gunilla
Abstract: It is well documented that more research can lead to hardened positions, particularly when dealing with complex, controversial, and value‐laden issues. This study is an attempt to unveil underlying values in a contemporary debate, where both sides use scientific evidence to support their argument. We analyze the problem framing, vocabulary, interpretation of evidence, and policy recommendations, with particular attention to the framing of nature and technology. We find clear differences between the two arguments. One side stress that there is no evidence that the present approach is causing harm to humans or the environment, does not ruminate on uncertainties to that end, references nature's ability to handle the problem, and indicates distrust in technological solutions. In contrast, the other side focuses on uncertainties, particularly the lack of knowledge about potential environmental effects and signals trust in technological development and human intervention as the solution. Our study suggests that the two sides' diverging interpretations are tied to their perception of nature: vulnerable to human activities versus robust and able to handle human impacts. The two sides also seem to hold diverging views of technology, but there are indications that this might be rooted in their perception of governance and economy rather than about technology per se. We conclude that there is a need to further investigate how scientific arguments are related to worldviews, to see how (if at all) worldview typologies can help us to understand how value‐based judgments are embedded in science advice, and the impact these have on policy preferences.